“Voice of anarchy”: Gender aspects of aggressive metal vocals. The example of Angela Gossow (Arch Enemy) - Florian Heesch (Criminocorpus)
Growling can be regarded as a key aesthetic practice of death metal. This practice, throughout the history of the genre, has been heavily gendered; while practiced both by men and women since the early 1990s it has nevertheless been associated with masculinity, due to its perceived aggressive sound, as well as corresponding notions of perceived low pitch and noise. In 2001 Angela Gossow became the singer of the band Arch Enemy and has since established herself as one of the most outstanding female growlers within the global metal scene. An analytical look at Gossow’s individual vocal style will be applied to argue that growling could potentially contribute to a more complex understanding of how voice, gender and aggression are related. This article examines the musical phenomenon of death metal growling, as well as the marginalization of women in what has been conceived as a primarily masculine style.